Teknik Operasi dan Faktor Risiko Residif Hernia Inguinalis Lateralis di RSU Cut Meutia Kabupaten Aceh Utara - Muhammad Sayuti; Cut Khairunnisa; Elsa Nur Salsabila; Jihan Haura; Rani Aprilita (Universitas Malahayati Lampung, 2023)
ABSTRACT Lateral inguinal hernia (HIL) is a protrusion of the contents of the abdominal cavity, which comes out of the peritoneal cavity through the internal inguinal ring which is located lateral to the inferior epigastric vessels. Risk factors for inguinal hernias are increased intra-abdominal pressure due to chronic cough, constipation, ascites or heavy lifting, when there is weakness of the abdominal wall muscles due to old age, pregnancy or prematurity, surgical incisions that cause incisional hernias and the presence of obesity. The principle of management of lateral inguinal hernia is animation and surgery. Operative treatment is the only rational treatment for inguinal hernias, namely carrying out hernia repairs both openly and laparoscopically. The purpose of this study was to determine surgical techniques and risk factors for recurrent lateral inguinal hernias at Cut Meutia Hospital, North Aceh District in 2018–2021. This study used a retrospective descriptive method with a cross sectional approach. The sample in this study were all patients diagnosed with recidive lateral inguinal hernias at Cut Meutia Hospital, North Aceh District recorded in 2018 to 2021 who met the inclusion and exclusion criteria. The results showed that the incidence of recurrent HIL was 8.5%, the most common risk factor was age ≥60 years (73.3%), male sex (100%), obesity (53.3%), history of strenuous activity (100 %), history of chronic cough (60%), history of urinary retention (26.7%), history of constipation (66.67%) and the first surgical technique used in 15 patients with residual HIL was 40% non-mesh graft and 60% with a mesh of corruption. Age, gender, obesity, history of strenuous activity, history of chronic cough, urinary retention and history of constipation are risk factors for recurrent lateral inguinal hernias at Cut Meutia Hospital, North Aceh District in 2018-2021. Keywords: Lateral Inguinal Hernia, Hernia Repair, Risk Factors ABSTRAK Hernia inguinalis lateralis (HIL) adalah penonjolan isi rongga perut, yang keluar dari rongga peritoneum melalui anulus inguinalis internus yang terletak lateral dari pembuluh epigastrika inferior. Faktor risiko terjadinya hernia inguinalis adalah peningkatan tekanan intra-abdominal karena batuk kronis, sembelit, asites atau angkat berat, ketika ada kelemahan otot dinding perut karena usia tua, kehamilan atau prematuritas, sayatan operasi yang menyebabkan hernia insisional dan adanya obesitas. Prinsip penatalaksanaan hernia inguinalis lateralis adalah konservatif dan operatif. Tindakan pengobatan operatif merupakan satu-satunya pengobatan hernia inguinalis yang rasional yaitu melakukan tindakan hernia repair baik secara open maupun laparoskopik. Tujuan penelitian ini untuk mengetahui teknik operasi dan faktor risiko hernia inguinalis lateralis residif di RSUD Cut Meutia Kabupaten Aceh Utara tahun 2018–2021. Penelitian ini menggunakan metode deskriptif retrospektif dengan pendekatan cross sectional. Sampel dalam penelitian ini adalah seluruh pasien yang terdiagnosis hernia inguinalis lateralis residif di RSUD Cut Meutia Kabupaten Aceh Utara yang tercatat pada tahun 2018 sampai 2021 yang memenuhi kriteria inklusi dan eklusi. Hasil penelitian menunjukkan kejadian HIL residif sebesar 8,5%, faktor risiko terbanyak pada usia ≥60 tahun (73,3%), jenis kelamin laki-laki (100%), obesitas (53,3%), riwayat aktivitas berat (100%), riwayat batuk kronis (60%), memiliki riwayat retensio urin (26.7%), riwayat konstipasi (66,67%) dan teknik operasi pertama yang digunakan pada 15 pasien HIL residif adalah 40 % non mesh graft dan 60% dengan mesh graft. Usia, jenis kelamin, obesitas, riwayat aktivitas berat, riwayat batuk kronis, retensio urin serta riwayat konstipasi merupakan faktor risiko hernia inguinalis lateralis residif di RSUD Cut Meutia Kabupaten Aceh Utara tahun 2018 – 2021. Kata Kunci: Hernia Inguinalis Lateralis, Hernia Repair, Faktor Risiko